Microstructure evolution and properties of dielectric magnesium titanate ceramic joints fabricated with bismuth glasses. Issue 18 (15th December 2020) - Chen, Qianqian; Jiang, Chonglai; Lin, Panpan; Du, Wumo; Lin, Jincheng; Wang, Ce; Xu, Jiujie; Lin, Tiesong; He, Peng
Abstract: Bismuth glasses with different Bi2 O3 and ZnO contents (designated as Bi15, Bi25, Bi36) were designed to investigate the interfacial microstructure evolution of magnesium titanate ceramic (MTC) joints. The mechanical and dielectric properties of joints were also studied. (Zn, Mg)2 TiO4 layer formed at the interface by the substitution reaction of Zn. Bi4 Ti3 O12 blocks generated at the interface of Bi15 glass seam due to low Bi2 O3 content, while Bi4 Ti3 O12 whiskers formed at the interface of Bi25 glass seam owing to the concentration gradient of Ti. Small Bi4 Ti3 O12 plate-like phases formed with a high concentration of [BiO6 ] and Ti, dispersing in the Bi36 glass seam. Rod-like MgSiO3 were produced at the interfaces of all glass seams. Besides, MgO phases formed in the Bi36 glass seam, owning to the increase of O 2− concentration. The shear strength of MTC/Bi36/MTC joints reached a maximum of 86.1 MPa under a combined effect of excellent matching and strengthening of small rod-like MgSiO3 and plate-like Bi4 Ti3 O12 . The dielectric and microwave dielectric properties were evaluated by the impedance analyser and the vector network analyser. The dielectric characteristics of MTC joints were similar to those of MTC base material. The microwave dielectric loss tangent of MTC joints was less than 0.09.